Çocuk Kalp Cerrahisi - Özışık, Kanat; Yılmaz, Mustafa; Özbay, Arif; Soran Türkcan, Başak; Kocabeyoğlu, Sinan Sabit; Tarhan, Orhan; Bahcıvan, Muzaffer; Gürbüz, H. Alper; Mercan, İlker and Uçar, Halil İbrahim and Atalay, Atakan and Ecevit, Ata Niyazi (Akademisyen Yayınevi Kitap DOI Portalı, 2023)
-